2017
DOI: 10.1371/journal.pone.0187945
|View full text |Cite
|
Sign up to set email alerts
|

Effects of periodontitis on the development of asthma: The role of photodynamic therapy

Abstract: To evaluate whether periodontitis modulates lung inflammation in an experimental model of asthma as well as the photodynamic therapy (PDT) is associated with a reduction of lung inflammation. Seventy-two BALB/c male mice (~2 months) were randomly divided into 8 groups (n = 9): Basal, Periodontitis (P), P+PT, P+PT+PDT, Asthma (A), A+P, A+P+PT, and A+P+PT+PDT. Periodontitis was induced by using the ligature technique and asthma was induced by ovalbumin (OVA). PT was performed with curettes and PDT with methylene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 67 publications
(95 reference statements)
1
13
0
Order By: Relevance
“…In asthmatic mice, an increase in the number of macrophages, lymphocytes, neutrophils, and eosinophils was found after conventional periodontal therapy. These results indicated that photodynamic therapy could induce a cellular immune response as shown by some other studies (31). Several studies have been performed to explain the role of oral bacteria in the pathogenesis of respiratory tract infections.…”
Section: Discussionsupporting
confidence: 74%
“…In asthmatic mice, an increase in the number of macrophages, lymphocytes, neutrophils, and eosinophils was found after conventional periodontal therapy. These results indicated that photodynamic therapy could induce a cellular immune response as shown by some other studies (31). Several studies have been performed to explain the role of oral bacteria in the pathogenesis of respiratory tract infections.…”
Section: Discussionsupporting
confidence: 74%
“…While this increased chance of asthma occurring in individuals with periodontitis has been T A B L E 2 Characteristics related to lifestyle and oral health conditions in individuals with severe asthma (case) and without asthma (control): corroborated by previous studies, 12,20 some studies were unable to identify this association, 21,22 or found an inverse association. The frequency of periodontitis in individuals with severe asthma was >3 times higher than in participants without this respiratory disease.…”
Section: Discussionmentioning
confidence: 89%
“…The frequency of periodontitis in individuals with severe asthma was >3 times higher than in participants without this respiratory disease. While this increased chance of asthma occurring in individuals with periodontitis has been T A B L E 2 Characteristics related to lifestyle and oral health conditions in individuals with severe asthma (case) and without asthma (control): corroborated by previous studies, 12,20 some studies were unable to identify this association, 21,22 or found an inverse association. 23,24 In accordance with the conceptual framework, the confounders were used to adjust the final association measurements to neutralize the influence of these covariables in the relationship between periodontitis and severe asthma.…”
Section: Discussionmentioning
confidence: 96%
“…The red light will act to improve tissue repair and decrease the periodontal inflammatory process, especially on facial swelling and trismus [22] and also will modulate the immunoinflammatory response of the host, interfering in the levels of inflammatory cytokines. Corrêa et al, [13] Candeo et al, [9] and Kellesarian et al [17] found a reduction of the pro-inflammatory cytokines IL1-β, IL-6, IL-8, and TNF-α after the PDT. So we will try to verify if PDT will promote advantageous modulation of cytokine levels in pericoronitis.…”
Section: Discussionmentioning
confidence: 99%
“…PDT relies on the appropriate combination of light, PS, and oxygen. [9] Light reach the PS at the target cell in the presence of oxygen, leading to PS excitation. [10] The singlet excited state PS molecules can be converted to a triplet excited state by intersystem crossing.…”
Section: Introductionmentioning
confidence: 99%